Murine model of oropharyngeal gastric fluid aspiration—A new assessment method for intrapulmonary liquid distribution using digital pixel calculation. (26th November 2017) - Beinart, Dylan; Finn, Sade M. B.; Scheuermann, Uwe; Holzknecht, Zoie E.; Barbas, Andrew S.; Parker, William; Lin, Shu S.
ABSTRACT: Aim of the Study : The aim of this study was to investigate a new method for visualization and quantification of intrapulmonary liquid distribution after oropharyngeal gastric fluid aspiration in mice. Material and Methods : Eleven mice received oropharyngeal aspiration with a gastric fluid, India ink, and saline solution. Digital imaging and pixel calculation were used to analyze intrapulmonary fluid distribution selectively. Results : Digital pixel analysis and orophanryngeal aspiration are both safe techniques in mice and deliver reproducible/valid results. Analysis revealed an average aspirate distribution of 86.8% of the total lung area. The proportional amount of the left lung was significantly greater than that of the right lung (P = 0.023). The lobe with the lowest mean distribution was the right lower lobe (79.2% ± 4.4%). Conclusion : Digital pixel calculation is a reliable method for quantitative, macroscopic evaluation of fluid distribution in the lung. This method is a useful tool for training purposes and it can be used to ensure interinvestigator reproducibility.